Arthroscopic Repair of the Hip Abductor Musculotendinous Unit: The Effect of Microfracture on Clinical Outcomes. Issue 6 (May 2021) - Kocaoglu, Baris; Paksoy, Ahmet Emre; Cerciello, Simone; Ollivier, Matthieu; Seil, Romain; Safran, Marc
Background: Endoscopic surgical repair has become a common procedure for treating patients with hip abductor tendon tears. Considering that retear rates are high after the repair of gluteus medius and minimus tendons, exploring alternative strategies to enhance structural healing is important. Purpose/Hypothesis: The purpose of this study was to evaluate the effect of adding microfracture to single-row repair (SR) on outcomes after the surgical repair of gluteus medius and minimus tendons and compare with SR and double-row repair (DR) without microfracture. We hypothesized that microfracture of the trochanteric footprint with SR would lead to superior clinical outcomes and lower clinically evident retear rates compared with SR and DR without the addition of microfracture. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 50 patients who underwent primary arthroscopic repair of hip gluteus medius and minimus tendon tears were investigated. Patients were divided into 3 groups: DR, 16 patients; SR, 14 patients; and SR with microfracture (SRM), 20 patients. Patients were evaluated with a visual analog scale (VAS) for pain as well as the Hip Outcome Score–Activities of Daily Living (HOS-ADL), Hip Outcome Score–Sport Specific (HOS-SS), and modified Harris Hip Score (mHHS) both preoperatively and at a minimum 2-year follow-up (mean, 30 months). Results: Among the SR, SRM, and DR groups, the greatest decrease in VAS scores and increase in mHHS, HOS-ADL, and HOS-SS scores were seen in the SRM group, and all the differences were significant ( P < .001 to P = .006). The abductor tendon retear rates were 31.3%, 35.7%, and 15.0% in the DR, SR, and SRM groups, respectively. Retear rates were lower in the SRM group compared with the SR and DR groups ( P = .042); however, there was no significant difference between the SR and DR groups ( P = .32) in terms of retear rates. Conclusion: Endoscopic SR with microfracture was a safe, practical, and effective technique and had the potential advantage of enhancing biological healing at the footprint. The addition of microfracturing the trochanteric footprint significantly lowered the retear rate and provided better functional outcomes than SR and DR without microfracture.